The phenomenon of the criminal's return to the crime scene: psychological analysis (based on F.M. Dostoevsky’s novel "Crime and Punishment") - G. E. Zaporozhtseva (Правоприменение, 2022)
Introduction. The reasons for the return of the criminal to the scene of the crime are analyzed using the plot of F.M. Dostoevsky's novel "Crime and Punishment", based on the theories of Freudianism and reflexology. The episode in that Rodion Raskolnikov returns to the crime scene became the reason for the author's long years of reflection on the criminal’s behavior mechanisms.The purpose of the study is to conduct a psychological analysis of Raskolnikov's behavior when he returns to the crime scene through the theories of Z. Freud and A.V. Dulov.The methodology. The author uses reflexology theories of I.P. Pavlov, V.M. Bekhterev, I.M. Sechenov, A.A. Ukhtomsky, the theory of person’s relations of V.N. Myasishchev, the theory of A.V. Dulov, the theory of Z. Freud, principles of systemacity, unity of consciousness and activity, causality, pleasure-displeasure, content analysis of Dostoevsky’s novel. The author uses empirical observations based from his own practical work in law enforcement.The main results, scope of application. An analysis of the determinants of the return to the crime scene of the main character of the novel "Crime and Punishment" through the psychoanalysis and reflexology was being undertaken for the first time. Based on the theory of A.V. Dulov about the impact of criminal activity on the increase in the mental stress of the criminal and guided by the theory of Z. Freud on the principle of pleasure-displeasure the author demonstrates on the example of Raskolnikov’s behavior that one of the reasons for the return of the criminal to the crime scene is the need to relieve mental stress determined by the consequences of the crime and getting pleasure from the discharge of an overstrained nervous system. This research is important both for theory and for law enforcement practice. The psychological analysis of criminal behavior outlined in the article will allow employees whose profession is related to solving crimes to look into criminal’s inner world, to predict the consequences of the crime that can be expressed in return of the criminal to the crime scene.Conclusions. The analysis of Rodion Raskolnikov's criminal behavior shows the psychological and criminological nature of the Dostoevsky’s novel. It can be argued that in the active activity of the criminal, after the commission of a crime, there is both a conscious and unconscious search for a mental discharge of an overstressed nervous system.